Pelatihan Peningkatan Sifat Individu Pendukung Kompetensi Petani Jagung Mandiri - Nurliza Nurliza (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2023)
TRAINING FOR IMPROVING PERSONAL TRAITS TO SUPPORT COMPETENCY OF CORN SMALHOLDERS. Corn smallholders frequently confront challenges in controlling and making appropriate farming decisions. They had low competence of farm management, smallholders intuitively emphasize the input cost aspect that causes high risk. The purpose of community service is conscientiousness, motivation, flexibility, positivity, and problem-solving of individual traits are increased using quantitative descriptive through counseling and practice for 20 corn smallholders of the